PEMBELAJARAN MATEMATIKA BERBASIS PROYEK DI KELAS IX SMP PADA MATERI TABUNG DENGAN KERAJINAN CELENGAN - Nuroh Kamilah; Syamsuri Syamsuri; Anwar Mutaqin (Universitas Muhammadiyah Semarang, 2023)
This research is motivated by mathematics which has a very important role in the development of scientific disciplines and developing human thinking. In mathematics there are several concepts, one of which is the concept of geometry. Geometry is still a difficult material for students, especially in the curved side of the cylinder. This causes the low learning achievement of students in the material. One of the learning models that can be used to improve mathematics learning outcomes is project-based learning. This learning model with a piggy bank project can foster a more active and creative learning attitude in students. This study aims to determine the effect of project-based learning on the mathematics learning outcomes of grade IX students on tube material using the piggy bank project. This research was conducted with a quantitative approach. The research model used was post-test only control group design. The population in this study were 9th grade students of SMPN 15 Kota Serang. This study involved two sample classes, namely class IX D as the experimental class and class IX E as the control class. The data collection technique used a test instrument consisting of 5 description questions. The data analysis used was descriptive and inferential statistical analysis. The results showed that there was a positive effect of project-based learning on math learning achievement.